DEVELOPMENT AND STANDARDIZATION OF GRANULES IN HARD GELATIN CAPSULES BASED ON THE COMPOSITION OF DRY EXTRACTS OF BIDENS TRIPARTITA, SOLIDAGO CANADENSIS L. AND AGRIMONIA EUPATORIA HERBS - E. K. Novikova; D. A. Chachin; I. E. Kaukhova; S. A. Minina (Разработка и регистрация лекарственных средств)
The aim of the study is the development and standardization of granules in hard gelatin capsules based on the composition of dry extracts of Bidens tripartita L., Solidago canadensis L. and Agrimonia eupatoria L. herbs, possessing nephroprotective activity and antifibrotics in toxic nephropathies. Developed the structure and defined the quality indicators of the pellets with dry extracts of Bidens tripartita L., Solidago canadensis L. and Agrimonia eupatoria L. herbs. The quality specification for the drug - granules of the composition of dry extracts in solid gelatin capsules is developed.